Impact of Bt transgenic cotton on population dynamics of aphids and natural enemies - UDIKERI, SHASHIKANT S; PATIL, B V; BASAVANAGOUD, K; KHADI, B M; KULKARNI, K A; VAMADEVAIAH, H M (The Indian Journal of Agricultural Sciences, 2012)
The dynamic aphids and its predator in RCH 2 Bt and non-Bt cotton hybrids was studied to know the effect of Cry toxin. The mean incidence of aphids was 23.82 and 21.37/ leaf in Bt and non-Bt cotton respectively indicating no significant variation. Mean population of coccinellids, Chrysoperla and syrphids was 0.89, 0.78 and 1.0/plant in RCH 2 Bt which was almost similar to the incidence on RCH 2 non Bt. There was strong and positive correlation between incidence of predators and aphid on both Bt and non- Bt cotton. The ‘r’ value for syrphids v/s aphids was 0.94 in RCH 2 Bt and 0.96 in non- Bt. The feeding assay with Bt intoxicated cotton leaves could not affect the biology and feeding potential of Chrysoperla.